Using synchrotron radiation to improve understanding of deformation of polycrystalline metals by measuring, modelling and publishing 4D information. (August 2019) - Greeley, D; Yaghoobi, M; Pagan, D; Sundararaghavan, V; Allison, J
Abstract: The evolution of deformation in a Mg-Nd alloy has been investigated using 3D HEDM and crystal plasticity simulation using the PRISMS-Plasticity CPFE Code. Using a simplified representative volume element (RVE), the average stress-strain response is well predicted by the PRISMS-Plasticity simulation. The distribution of the resolved shear stresses corresponding to the basal mode for all grains is obtained using both HEDM and the CPFE. simulation. The results show that the CPFE predicted substantially narrower distributions, thus indicating the need for improved digital representation of the RVE. The results of these HEDM experiments and PRISMS-Plasticity simulations have been stored in the Materials Commons in a straight-forward manner and are being made available as a published dataset. Both PRISMS-Plasticity and the Materials Commons are open-source and available for use by the global materials community.